Bioactive (+)-Catechin-3ꞌ-O-rhamnopyranoside from Neocarya macrophylla (Sabine) Prance (Chrysobalanaceae). Issue 1 (2nd January 2019) - A. J., Yusuf; M. I., Abdullahi; A. M., Musa; A. K., Haruna; V., Mzozoyana; H., Abubakar
ABSTRACT: In this study, a flavan-3-ol glycoside, (+)-catechin-3ꞌ- O -rhamnopyranoside isolated from the stem bark extract of N. macrophylla was evaluated for its antivenom, analgesic, anti-inflammatory, and antimicrobial activities. The compound (at 1, 5 and 10 mg/kg) was able to protect mice against lethality induced by Naja nigricollis venom with 100%, 40%, and 20% survival rate, respectively; it was also found to be 33.7% effective in combating the hydrolytic actions of N. nigricollis PLA2 enzyme; the compound (at 2.5 and 10 mg/kg) exhibited significant ( p < 0.05 ) analgesic effect in the formalin test which was higher than that observed by the standard drug, piroxicam (10 mg/kg) and there was 45.0% and 41.2% inhibition of inflammation by the compound at the 3rd & 4th hours. In addition, the compound was found to be effective against S. aureus, VRE, S. feacalis, E. coli, P. aeruginosa, P. vulgaris, C. albicans, and C. krusei with mean zone of inhibition ranged between 28 and 36 mm and an MIC and MBC/MFC values ranging from 6.25 to 25.0 µg/mL and 12.5–50.0 µg/mL, respectively. Thus, bioactivities of (+)-catechin-3ꞌ- O -rhamnopyranoside were reported for the first time.